Fronteras, integración, cooperación y desarrollo regional (2016)
Both the analysis of the problems of border areas, such as the proposed strategies and policies border development particularly in the Latin American and Colombian level, require framed in concepts that exceed schemes that favor neighboring and administrative problems as fundamentals binational surrounding areas. In this paper a reflection on the relationship between regional development, integration and cooperation, taken as analytical references to determine the strategies and policies that will effectively convert the border areas and the population inhabiting them exposed objects and also subjects of economic and social development articulated national development.